PENERAPAN METODE MUHASABAH AN-NAFS DALAM PEMBENTUKAN AKHLAKUL KARIMAH SANTRI DI PONDOK PESANTREN AL-HIKMAH MUHAMMADIYAH SUKOHARJO TAHUN PELAJARAN 2022/2023 - Indah Muslimah; Isfihani; Praptiningsih (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
Contemporary phenomenon, if we pay attention together that the morals of students who have grown up or are teenagers are very concerning, there are many cases that we meet directly or are spread on social media regarding the moral behavior of teenagers today. Many of them do not reflect themselves as a Muslim who is moral and well behaved. One example of students who are brave with teachers, teachers who should be respected and valued but there are still students who don't listen to their teacher's advice and still behave poorly towards their teacher and their friends. This study aims to determine the effectiveness of the application of the muhasabah an-nafs method in the formation of akhlakul karimah. In this study using a qualitative descriptive method, namely analyzing events and understanding existing phenomena then creating a comprehensive and complex picture. The results of this study show that the muhasabah an-nafs method in the formation of akhlakul karimah plays an important role because with this program students can self-introspect from what students have done. With muhasabah an-nafs students can also increase the good deeds that have been done can be increased in the future both in quality and quantity.